Harnessing cross-border resources to confront climate change. Issue 87 (September 2018) - Aburto-Oropeza, Octavio; Johnson, Andrew F.; Agha, Mickey; Allen, Edith B.; Allen, Michael F.; González, Jesús Arellano; Arenas Moreno, Diego M.; Beas-Luna, Rodrigo; Butterfield, Scott; Caetano, Gabriel; Caselle, Jennifer E.; Gaytán, Gamaliel Castañeda; et al.
Abstract: The US and Mexico share a common history in many areas, including language and culture. They face ecological changes due to the increased frequency and severity of droughts and rising energy demands; trends that entail economic costs for both nations and major implications for human wellbeing. We describe an ongoing effort by the Environment Working Group (EWG), created by The University of California's UC-Mexico initiative in 2015, to promote binational research, teaching, and outreach collaborations on the implications of climate change for Mexico and California. We synthesize current knowledge about the most pressing issues related to climate change in the US-Mexico border region and provide examples of cross-border discoveries and research initiatives, highlighting the need to move forward in six broad rubrics. This and similar binational cooperation efforts can lead to improved living standards, generate a collaborative mindset among participating universities, and create an international network to address urgent sustainability challenges affecting both countries.